Programa educativo de liderazgo familiar en directivos y padres de familia en la prevención de la deserción escolar en la institución educativa primaria secundaria N° 60152 comunidad Pihuicho Isla distrito Fernando Lores 2022 - Reátegui Malafaya de Pinedo, Luisa Stefani (2023)
Results are presented in relation to the investigation after the application of an educational program in search of improving the prevention of school dropout in an educational institution, the research problem was formulated: What is the effect of the application of the educational program of family leadership in the primary secondary educational institution No. 60152 Pihuicho Isla, Fernando Lores?, the hypothesis that the application of a family leadership educational program in managers and parents significantly improves the prevention of school dropout and as a general objective to evaluate the effect of the application of the educational program of family leadership in managers and parents in the prevention of school dropout in the aforementioned educational institution. The type of research is evaluative, with a longitudinal, univariate, field, and quasi-experimental design with an experimental and control group. 100 managers and teachers made up the population and 50 the sample, 25 of them being the experimental group and 25 the control group. The survey technique and a performance test were applied, an instrument validated by experts. It is concluded that the evaluation of the effect of the application of the educational program of family leadership in managers and parents in the prevention of school dropout, before the application of the program to 8.56% of the experimental group and 8, 72% of the control group with knowledge of dropout prevention, after the application of the program increases in improvements in prevention to 18.12% of the experimental group while the control group improves 11.24%.